Chemical behavior of Cd, Pb and their interaction in rhizosphere and bulk - LIN Qi; CHEN Huai-man; ZHENG Chun-rong; CHEN Ying-xu (浙江大学学报. 农业与生命科学版, 2000)
The present paper deals with the chemical behavior of Pb, Cd and their interaction in rhizosphere and bulk after growing plants (rice or wheat) using a rhizobox or rhizobag. The main results were as follows: The contents of Pb extractable in both rice and wheat rhizosphere of the red soils, were higher than those in the bulk soils, which demonstrated the Pb was activated in rhizosphere due to the activity of roots and the action of microorganisms on the root surface and in the rhizosphere. The content of Cd extractable in the rice rhizosphere of the two soils, however were lower than those in the bulk soils, probably due to large amount of Cd in rhizosphere which was absorbed by rice plants.